Prevalence and Characterization of Food-Borne Vibrio parahaemolyticus From African Salad in Southern Nigeria - Igbinosa, Etinosa O.; Beshiru, Abeni; Igbinosa, Isoken H.; Ogofure, Abraham G.; Uwhuba, Kate E. (Frontiers in Microbiology, 2021)
The demand for minimally processed vegetables (African salad) has increased partly due to its inclusion in ready-to-eat foods. Nevertheless, the associated risk of the presence of emergent foodborne pathogens, such as Vibrio parahaemolyticus might be underestimated. The present study was designed to isolate and characterize foodborne V. parahaemolyticus from minimally processed vegetables using culture-based methods and molecular approach. A total of 300 samples were examined from retail outlets between November 2018 and August 2019 from Southern Nigeria. The prevalence of vibrios from the overall samples based on the colonial proliferation of yellow, blue-green and/or green colonies on thiosulfate citrate bile salts sucrose agar was 74/300 (24.6%). An average of two green or blue-green colonies from respective plates was screened for V. parahaemolyticus using analytical profile index (API) 20 NE. Polymerase chain reaction further confirmed the identity of positive V. parahaemolyticus. The counts of V. parahaemolyticus ranged from 1.5 to 1,000 MPN/g. A total of 63 recovered V. parahaemolyticus were characterized further. The resistance profile of the isolates include ampicillin 57/63 (90.5%), cefotaxime 41/63 (65.1%), ceftazidime 30/63 (47.6%), amikacin 32/63 (50.8%), kanamycin 15/63 (23.8%), and oxytetracycline 16/63 (25.4%). The multiple antibiotic index ranged from 0–0.81. The formation of biofilm by the isolates revealed the following: strong formation 15/63 (23.8%), moderate formation 31/63 (49.2%), weak formation 12/63 (19.1%), and no formation 5/63 (7.9%). A total of 63/63 (100%), 9/63 (14.3%), and 20/63 (31.8%) of the isolates harbored the tox R gene, TDH-related hemolysin (trh) and thermostable direct hemolysin (tdh) determinants respectively. The isolates with O2 serogroup were most prevalent via PCR. Isolates that were resistant to tetracycline, kanamycin, and chloramphenicol possessed resistant genes. The presence of multidrug-resistant vibrios in the minimally processed vegetables constitutes a public health risk and thus necessitates continued surveillance.